The Usefulness of New Body Indices in Determining the Risk of Cardiovascular Disease in Cases with Obstructive Sleep Apnea Syndrome - Yeşildağ M; Şentürk Z; Bekci TT; Guney İ (International Journal of General Medicine)
Mihrican Yeşildağ,1 Zühal Şentürk,1 Taha Tahir Bekci,1 İbrahim Guney2 1Department of Chest Diseases S.B University Konya Training and Research Hospital, Konya, Turkey; 2Department of Nephrology, S.B University Konya Training and Research Hospital, Konya, TurkeyCorrespondence: Mihrican Yeşildağ, Department of Chest Diseases, S.B University Konya Training and Research Hospital, Konya, 42090, Turkey, Tel +90 5057728296, Email mihricanysd@hotmail.comPurpose: Obstructive Sleep Apnea Syndrome (OSAS) is considered a notable independent risk factor for cardiometabolic disorders. The current study aimed to investigate the efficacy of new anthropometric indices, A Body Shape Index (ABSI) and the Body Roundness Index (BRI), in assessing cardiovascular risk (CVR) and cardiovascular disease (CVD) among OSAS patients and to compare them with traditional indices.Materials and Methods: The records of 281 patients who consulted our sleep center were retrospectively reviewed. Patients were categorized according to OSA severity using AHI values. They were also classified based on cardiovascular conditions (CVR and CVD). ABSI, BRI, and traditional indices [such as body mass index (BMI), neck circumference (NC)] of the patient groups were evaluated.Results: Of the 281 patients recruited, 218 (77.6%) were diagnosed with OSAS. The distribution of cardiovascular conditions among the OSAS patients was: CVD (20%), CVR (39.8%), and control (40.2%). The new index BRI (Odds ratio-OR: 2.641, 95% CI: 1.24– 5.62) has shown better predictive ability for CVR compared to traditional measures, while NC (OR: 1.320, 95% CI: 1.09– 1.60) was the only predictor of CVD. Additionally, the BRI had a higher AUC value (0.656) than traditional indices in terms of diagnostic performance in distinguishing CVR. Another new index ABSI was not found to be significant in evaluating cardiovascular conditions.Conclusion: BRI, one of the new indices, is a useful anthropometric parameter in the CVR assessment of OSAS patients, offering better predictive ability than traditional measurements.Keywords: anthropometric indices, abdominal obesity, body roundness index, cardiovascular risk, cardiovascular disease, obstructive sleep apnea syndrome